10 year follow-up study of gender in sports coverage of the U.S. and Spanish online newspapers (2003-2004 vs. 2013-2014) - Jillian E. Frideres; José M. Palao (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2019)
The purpose of this paper was to assess the evolution of sports coverage regarding gender in online newspapers in two western societies Spain and the United States, in a period of ten years (2004 vs. 2014). A total of 2,951 articles with athletic content from the online newspapers usatoday.com and elmundo.es were analyzed. The variables registered were gender, placement in the newspaper, word count, inclusion of photographs, and the sports disciplines. The results show a significant reduction in sports articles in the two online newspapers for both genders. This reduction resulted in a decrease in the variability of sports articles. Further, there was a significant imbalance in sports news between the two genders. There was a significant reduction in the proportion of sports articles in both online newspapers for women, significantly reducing the accessibility of articles about women's sports. The gender imbalance was higher in the Spanish newspaper than in the U.S. newspaper. The gender imbalance was higher in the Spanish newspaper than in the U.S. newspaper. Both online newspapers showed an image of sport that is male-orientated, focused on elite-level sport and with an overall low number of sport disciplines.